Regression of Nevi After Candida Injection for the Treatment of Verruca Vulgaris. Issue 2 (16th December 2016) - Kollmann, Emily; Cleaver, David; Cleaver, Lloyd; Cleaver, Jonathan
Abstract: The most common treatment methods for verruca vulgaris are destructive methods that are often painful and treat individual verruca. Thus immune modulators, including Candida immunotherapy, are used to treat persistent recalcitrant and multiple verrucas simultaneously. Very few side effects are reported with Candida immunotherapy; they include vitiligo and now halo nevi. Physicians need to be aware of and discuss side effects with patients undergoing Candida immunotherapy.